2010
DOI: 10.3109/09513590.2010.489131
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal therapy with estradiol and testosterone implants: bone protection?

Abstract: BMD variance between the groups in the period of 1 year showed that the combination of estradiol and testosterone promoted bone protection in post menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Considering potential long-term effects of HRT implants, preliminary studies indicate a significant protective role for bone health. [11][12][13][14][15] Larger studies confirming bone and cardiovascular outcomes, are required including for women with POI.…”
Section: Discussionmentioning
confidence: 99%
“…Considering potential long-term effects of HRT implants, preliminary studies indicate a significant protective role for bone health. [11][12][13][14][15] Larger studies confirming bone and cardiovascular outcomes, are required including for women with POI.…”
Section: Discussionmentioning
confidence: 99%
“…Britto, et al studied 61 Brazilian patients in prospective cohort study using implants of E and T. BMD assessment through Dual energy X-ray absorptiometry showed addition of 1.87% in the lumbar spine and 3.8% in the neck of femur BMD in women using impants, and decrease in BMD lumbar of 5.92%, and 5.06% in the neck of femur, without implants, after 1 year [1].…”
Section: Discussionmentioning
confidence: 99%
“…During menopause, women may experience greater loss of bone mineral density, leading to a high risk of fractures and their consequences for patients in this stage of life. Estradiol (E) has great importance in the maintenance of bone micro architecture and E and testosterone (T) combination have high effectiveness in preventing osteoporosis and fractures in post menopausal women [1].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we know that the combination of androgens and estrogens for hormone replacement therapy in menopausal women is associated with increased bone mass above that observed with estrogen alone (CasteloBranco et al, 2000). A cohort study developed to assess BMD in postmenopausal women using estradiol and testosterone hormonal implants comparing to that of patients without hormonal therapy, confirmed that BMD variance between the groups in the period of 1 year was significantly different, and concluded that the combination of estradiol and testosterone promoted bone protection in postmenopausal women (Britto et al, 2011). Androgen receptors have been identified in osteoblasts, osteoclasts and osteocytes.…”
Section: Androgens and Bonementioning
confidence: 97%